A reorientação do fluxo de transporte rumo ao norte do Brasil - Campos, Carlos Eduardo Espinel (Universidade Federal de São Carlos, 2017)
The objective of this research is to analyze the economic impacts of the reorientation of the national transport flow towards the ports of the North, as it is currently concentrated in the ports located in the South and Southeast of the country. Through an analysis of the freight prices and export volume of the soybean from the Central West Region to the ports of the North and South and Southeast of Brazil, it was possible to establish efficiency gains, which supported the shocks applied through a computable general equilibrium model, to identify the direct and indirect effects of this possible reorientation trough North. The results indicated that there are gains caused by a possible redirection of the transport flow, however, as a rule, they concentrate income and benefit mostly the Central West Region. Thus, competitive gains obtained by this region are in detriment of the other regions of the country. In addition, the economic impacts of the shocks did not present a high intensity, since the "transport" input, where the efficiency shock was applied, is only one among the various inputs used in soybean production. The alternative of increasing the transport flow trough the North has been shown effective, but not enough to fix the logistical deficit that challenges the Brazilian agribusiness performance. Therefore it is necessary to combine this reorientation with other measures that may bring greater dynamism to the country.
Regional impacts of the increasing grain exporting flow through Brazilian Northern ports
Keywords: Soja; Fretes; Modelo de Equilíbrio Geral Computável; Soybean; Freights; Computable General Equilibrium Model; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA REGIONAL E URBANA::ECONOMIA REGIONAL; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA REGIONAL E URBANA; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIAS AGRARIA E DOS RECURSOS NATURAIS; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::METODOS QUANTITATIVOS EM ECONOMIA